2015
DOI: 10.22256/pubvet.v6n31.1452
|View full text |Cite
|
Sign up to set email alerts
|

Medidas para avaliar o conforto térmico em aves

Abstract: ResumoAtualmente, os avanços obtidos na área de avicultura têm sido limitados por fatores ambientais, principalmente pelo ambiente aos quais os animais são submetidos, portanto, seu monitoramento e controle são essenciais para o sucesso dessa atividade. As aves são animais homeotermos, apresentando a capacidade de manter a temperatura interna constante e este processo só é eficiente quando a temperatura ambiente estiver dentro dos limites de termoneutralidade, que está relacionada a um ambiente térmico ideal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 4 publications
1
8
1
12
Order By: Relevance
“…The values in the present study were lower than those reported by Costa et al (2012), who studied physiological indicators in the production of broiler chickens and observed minimum and maximum RR of 46.83 and 58.96 mov min -1 , respectively. In comparison to laying hens and broiler chickens, quails have physiological characteristics very similar to those of chickens, which is the reason why they are usually subjected to the same management practices.…”
Section: Resultscontrasting
confidence: 96%
“…The values in the present study were lower than those reported by Costa et al (2012), who studied physiological indicators in the production of broiler chickens and observed minimum and maximum RR of 46.83 and 58.96 mov min -1 , respectively. In comparison to laying hens and broiler chickens, quails have physiological characteristics very similar to those of chickens, which is the reason why they are usually subjected to the same management practices.…”
Section: Resultscontrasting
confidence: 96%
“…A zona de termoneutralidade está relacionada a um ambiente térmico ideal no qual as aves encontram condições perfeitas para expressar suas melhores características produtivas (Nazareno et al, 2009). Segundo Baeta & Souza (2010) a zona de conforto térmico deve estar entre 20 e 30 o C e, havendo estresse térmico, o desempenho das aves pode ser afetado, acarretando diminuição da ingestão de alimento e das atividades físicas, além de perdas na produção, tais como diminuição na quantidade de ovos produzidos, aumento dos ovos com má formação e até o óbito das aves (Vitorasso & Pereira, 2009;Costa et al, 2012;.…”
Section: Palavrasunclassified
“…Assim, a identificação dos fatores que influenciam na vida do animal, como o estresse, imposto pelas flutuações estacionais do ambiente, permite ajustes nas práticas de manejo possibilitando dar-lhes sustentabilidade e viabilidade econômica (Costa et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Thus, the knowledge of the factors that influence in the animal's performance, such as stress, imposed by seasonal fluctuations of the environment, allows adjustments in management practices, enabling to give them sustainability (COSTA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%